2016
DOI: 10.1155/2016/4894653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Irradiance Light-Curing on Micromechanical Properties of Resin Cements

Abstract: This study investigated the influence of light-curing at high irradiances on micromechanical properties of resin cements. Three dual-curing resin cements and a light-curing flowable resin composite were light-cured with an LED curing unit in Standard mode (SM), High Power mode (HPM), or Xtra Power mode (XPM). Maximum irradiances were determined using a MARC PS radiometer, and exposure duration was varied to obtain two or three levels of radiant exposure (SM: 13.2 and 27.2 J/cm2; HPM: 15.0 and 30.4 J/cm2; XPM: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…One study stated it was followed the LCU manufacturer’s protocol without specifying the procedure [ 27 ]. Thirteen studies reported in detail the irradiation technique applied [ 10 , 11 , 14 , 16 , 17 , 21 , 22 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study stated it was followed the LCU manufacturer’s protocol without specifying the procedure [ 27 ]. Thirteen studies reported in detail the irradiation technique applied [ 10 , 11 , 14 , 16 , 17 , 21 , 22 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the curing combination of standard irradiance & exposure significantly outperformed standard irradiation & short exposure and high irradiance & ultra-short exposure combinations [ 14 ]. The hardness (KHN value) parameter was examined in seven studies [ 15 , 16 , 17 , 27 , 28 , 31 , 33 ]. In accordance with DC values, equivalent or higher degree of microhardness values of resin composites were achieved when 1200 mW/cm 2 was used compared to 3600 mW/cm 2 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All data were collected at 25 °C ± 1 °C and 60 ± 5% humidity conditions and shielded from ambient and room light. Before the measurements, all specimens were placed in the dark for 15 min [ 21 ]. According to the statistical analysis, when the mean value of HV and DC of certain experimental groups did not have significantly different mean values of HV and DC from that of the control group, the minimum RE of the experimental groups was considered the minimum RE to trigger an adequate polymerization of the resin cements.…”
Section: Methodsmentioning
confidence: 99%